Das Zeichen der Vier Ian Richardson in Sherlock Holmes ; Mörder, Geheimnisse, Intrigen ... - Doyle, Arthur Conan 1859-1930 ([dtp entertainment], 2014)
A beautiful young woman seeks the help of Holmes and Watson when the mysterious benefactor who has been sending her a pearl each year since her father disappeared wants to meet her. Involved are a priceless hoard of Indian treasure and a murderer, whose trademark is "the sign of four."
Orig.: UK 1983
Keywords: Holmes, Sherlock / Drama; Holmes, Sherlock; Watson, John H. / (Fictitious character); Watson, John H. (Fictitious character) / Drama; Film; DVD-Video